Pengembangan Sistem Informasi Layanan Surat sebagai Sarana Pelayanan Administrasi Publik Berbasis Web dan Whatsapp Bot di Desa Pondokrejo - Annurdien Rasyid; Handaru Jati (Journal of Information Technology and Education (JITED), 2025)
This study aims to: (1) develop a web-based information system and WhatsApp bot to allow residents to handle letter administration outside of Desa Pondokrejo office hours; (2) develop a web-based information system and WhatsApp Bot with a user-friendly and interactive interface that is tested in terms of functional suitability and usability aspects. This research uses the R&D research method. The development procedure in this study uses the Rational Unified Process (RUP) development model. Testing and data collection for this research were conducted in Desa Pondokrejo. The subjects of this study were 12 Desa Pondokrejo officials and 34 residents of Desa Pondokrejo. The data collection technique in this study uses a questionnaire. The research instrument in this study uses the testing aspect of ISO/IEC 25010, which consists of functional suitability and usability. The data analysis technique in this study uses quantitative calculations in the form of percentage calculations. The results of this study indicate that: (1) The web-based letter administration information system and WhatsApp bot named Sipuas have been successfully created and all features run according to their functions; (2) The web-based letter administration information system and WhatsApp bot named Sipuas have been tested using the ISO/IEC 25010 software testing. The test results on the functional suitability aspect obtained a percentage of 100% in expert testing. In terms of usability, Sipuas scored 79% for web admin and 88% for the WhatsApp bot. All these tests indicate that the Sipuas application is good or suitable for use.